THE PREPARATORY INVESTIGATION IN THE CRIMES OF CORRUPTION OF OFFICIALS IN THE NEW CRIMINAL PROCEDURE CODE - M. Dubcek Dueñas Zúñiga (2020)
The way to solve impunity for crimes against Public Administration as a goal of Criminal Law in our national situation, will always be latent, to be able to fight, corruption needs to be shown. Through the complaint, the acts of corruption come to light to be investigated and punished In the present investigation we must aim to determine the importance of the preparatory investigation stage in crimes of corruption of officials within the framework of the New Criminal Procedure Model and the relationship between the beginning of the Preliminary Investigation and the formalization of the Preparatory Investigation in the judicial district of Puno, to identify how the fiscal disposition that declares the continuation and formalization of the preparatory investigation contributes to due process with incidence on the object and purpose of the criminal process, to deepen the analysis and interpretation carried out in the Preliminary Investigation. For the elaboration of the research work, the correlational and quantitative descriptive method was used, in turn applying the survey as an instrument; Taking as a hypothesis that the judges and trial lawyers surveyed perceive that the declaration of formalization of the preparatory investigation has significant importance and significance to move to the intermediate stage of the criminal process in the preparatory investigation courts of the judicial district of Puno.